OPTIMIZATION OF A TECHNOLOGICAL PROCESS FOR HEAT TREATMENT OF CU99.9 WITH DIFFERENT DEGREES OF PLASTIC DEFORMATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Different degrees of plastic deformation of Cu99.9 have been achieved by using different technological forming processes. Recrystallization annealing was carried out at different time-temperature regimes. The influence of the degree of plastic deformation and the recrystallization annealing conditions on the structure of the studied material (Cu99.9) is discussed. The technological process of heat treatment is optimized.